2020
DOI: 10.1038/s41598-020-68509-x
|View full text |Cite
|
Sign up to set email alerts
|

CT features of COVID-19 patients with two consecutive negative RT-PCR tests after treatment

Abstract: The objective of this study is to expound the CT features of COVID-19 patients whose throat swab samples were negative for two consecutive nucleic acid tests after treatment. We retrospectively reviewed 46 COVID-19 patients with two consecutive negative RT-PCR tests after treatment. The cases were divided into moderate group and severe/critical group according to disease severity. Clinical and CT scanning data were collected. CT signs of pulmonary lesions and the score of lung involvement were expounded. Thirt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 13 publications
1
29
0
2
Order By: Relevance
“…According to eight observational studies, the location of reported pleural effusions was unilateral in 66.8% (443/663) of cases, with the remainder bilateral in 33.2% (220/663) of patients. 13 , 14 , 15 , 16 , 17 , 18 , 19 In the two largest observational studies included in our review by Majidi et al and Feng et al, the incidence of pleural effusions were 7.6% and 5.7% among 552 and 442 COVID-19 patients, respectively. 20 , 21 A high incidence of pleural effusions ranging from 13.3% to 62.5% was reported in 14 observational studies reviewed ( Table 1 ).…”
Section: Incidence Of Covid-19-related Pleural Effusionmentioning
confidence: 74%
See 3 more Smart Citations
“…According to eight observational studies, the location of reported pleural effusions was unilateral in 66.8% (443/663) of cases, with the remainder bilateral in 33.2% (220/663) of patients. 13 , 14 , 15 , 16 , 17 , 18 , 19 In the two largest observational studies included in our review by Majidi et al and Feng et al, the incidence of pleural effusions were 7.6% and 5.7% among 552 and 442 COVID-19 patients, respectively. 20 , 21 A high incidence of pleural effusions ranging from 13.3% to 62.5% was reported in 14 observational studies reviewed ( Table 1 ).…”
Section: Incidence Of Covid-19-related Pleural Effusionmentioning
confidence: 74%
“…Pleural retraction was only noted in three observational studies with a reported incidence of 41.7% (75/180). 14 , 32 , 46 Although pleural thickening was commonly observed in elderly COVID-19 patients who were age 60 years and older (71.4% versus 40.9%; p = 0.011), which might indicate higher disease severity such as ARDS with greater radiologic lung involvement, the incidence of pleural traction and effusion remained similar, regardless of age group. 47 In SARS patients, chest imaging during the late-stage of ARDS (two weeks and more) consisting of lung fibrosis and pleural thickening/retraction are similar to those seen in late-stage ARDS from alternative etiologies.…”
Section: Incidence Of Covid-19-related Pleural Effusionmentioning
confidence: 96%
See 2 more Smart Citations
“…CT is also used during short-term follow-up of COVID-19 for clinical decision making to monitor the course of pneumonia in hospitalized patients, and it can also be used in symptomatic patients for long-term follow-up, as it can reveal late lung alterations [ 29 , 108 , 113 , 114 , 115 , 116 ]. Fu et al [ 117 ] suggested that CT was better than nucleic acid conversion in assessing final treatment outcomes. The diagnostic value of CT decreases in cases of low prevalence of COVID-19 disease [ 101 ].…”
Section: Chest Ctmentioning
confidence: 99%